2021
DOI: 10.1186/s12902-021-00851-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between overweight/obesity and double diabetes in adults with type 1 diabetes; a cross-sectional study

Abstract: Background Double Diabetes (DD), type 1 diabetes (T1DM) + insulin resistance (IR), is associated with increased risk of micro/macro-vascular complications and mortality. Obesity can contribute to the development of DD. This study explored the prevalence of overweight/obesity and their association with DD in adults with T1DM. Methods Cross-sectional study of consecutive adults with T1DM attending diabetes clinics in a secondary care hospital (Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
3
8
1
Order By: Relevance
“…Our data did not show an association between overweight/obesity with HbA1c levels or with the number of patients that reached the targets for good glycemic control, similar to data found in another study [ 39 ], in which patients with overweight/obesity used higher daily insulin doses compared to patients without overweight/obesity, but also with no difference in HbA1c levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data did not show an association between overweight/obesity with HbA1c levels or with the number of patients that reached the targets for good glycemic control, similar to data found in another study [ 39 ], in which patients with overweight/obesity used higher daily insulin doses compared to patients without overweight/obesity, but also with no difference in HbA1c levels.…”
Section: Discussionsupporting
confidence: 90%
“…Controversial results have been described in patients with T1D with overweight/obesity concerning glycemic control [ 8 , 39 ]. The DCCT showed that independent of the weight gain, patients under intensive insulin treatment achieved the same HbA1c levels during the follow-up [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence for the role of obesity in the increased incidence of type 1 diabetes mellitus (T1DM), with studies from North America and the UK suggesting an increasing prevalence of overweight and obesity in people with T1DM. [ 24 ] It has been hypothesised that obesity-induced insulin resistance may be responsible for the accelerated loss of pancreatic β cells through excessive stimulation[ 25 ] and a chronic proinflammatory state. [ 26 ] This causal role is supported by MR studies, although the evidence is not as consistent (compared to obesity and T2DM), with high heterogeneity between the studies.…”
Section: Evidence For Causal Role Of Excess Adiposity On Obesity-rela...mentioning
confidence: 99%
“…There are approximately 400 000 people with type 1 diabetes (T1D) in the United Kingdom, with rates increasing by 4% annually 1. T1D is associated with a healthy bodyweight; however, overweight and obesity is becoming increasingly common in this population due, in part, to modern more intensive approaches to manage hyperglycaemia with higher daily doses of insulin, as evidenced by the Diabetes Control and Complications Trial, and other studies 2 3. The prevalence of obesity (body mass index (BMI) ≥30 kg/m 2 ) in adults with T1D from the Pittsburgh Epidemiology of Diabetes Complications Study increased from 3.4% at baseline (1986–1988) to 22.7% (2004–2007) 4.…”
Section: Introductionmentioning
confidence: 99%